Liver Transplantation for Hepatocellular Carcinoma: Malatya Experience - Ince, V; Akbulut, AS; Otan, E; Ersan, V; Karakas, S; Sahin, TT; Carr, BI; Baskiran, A; Samdanci, E; Gozukara, H; Koc, C; Usta, S; et al. (2020)
Survival was examined from a Turkish liver transplant center of patients with HCC, to identify prognostic factors. Data from 215 patients who underwent predominantly live donor liver transplant for HCC at our institute over 12 years were included in the study and prospectively recorded. They were 152 patients within and 63 patients beyond Milan criteria. Patients beyond Milan criteria were divided into two groups according to presence or absence of tumor recurrence. Recurrence-associated factors were analyzed. These factors were then applied to the total cohort for survival analysis. We identified four factors, using multivariate analysis, that were significantly associated with tumor recurrence. These were maximum tumor diameter, degree of tumor differentiation, and serum AFP and GGT levels. A model that included all four of these factors was constructed, the 'Malatya criteria.' Using these Malatya criteria, we estimated DFS and cumulative survival, for patients within and beyond these criteria, and found statistically significant differences with improved survival in patients within Malatya criteria of 1, 5, and 10-year overall survival rates of 90.1%, 79.7%, and 72.8% respectively, which compared favorably with other extra-Milan extended criteria. Survival of our patients within the newly defined Malatya criteria compared favorably with other extra-Milan extended criteria and highlight the usefulness of serum AFP and GGT levels in decision-making. C1 [Ince, Volkan; Akbulut, A. Sami; Otan, Emrah; Ersan, Veysel; Karakas, Serdar; Sahin, Tolga Tevfik; Carr, Brian, I; Baskiran, Adil; Koc, Cemalettin; Usta, Sertac; Ozdemir, Fatih; Barut, Bora; Gonultas, Fatih; Sarici, Baris; Kutluturk, Koray; Dogan, Murat Sait; Ozgor, Dincer; Dirican, Abuzer; Aydin, Cemalettin; Isik, Burak; Ara, Cengiz; Kayaalp, Cuneyt; Emre, Sukru; Yilmaz, Sezai] Inonu Univ, Liver Transplantat Inst, Dept Surg, TR-44315 Malatya, Turkey. [Samdanci, Emine] Inonu Univ, Med Sch, Dept Pathol, Malatya, Turkey. [Gozukara, Harika] Inonu Univ, Med Sch, Dept Bioistat, Malatya, Turkey. [Dikilitas, Mustafa] Inonu Univ, Med Sch, Dept Med Oncol, Malatya, Turkey. [Harputluoglu, Murat; Aladag, Murat] Inonu Univ, Med Sch, Dept Gastroenterol, Malatya, Turkey. [Kutlu, Ramazan] Inonu Univ, Med Sch, Dept Radiol, Malatya, Turkey. [Varol, Ilknur] Inonu Univ, Med Sch, Dept Pediat Gastroenterolgy, Malatya, Turkey.